Analysis of Implementation of EWSS (Early Warning Score Systems) Against AvLos (Average Length of Stay) and the Trust of Patients in Inpatient Installation at Jombang General Hospital - Sutikno Sutikno; Sandu Siyoto; Byba Melda Suhita (Journal for Quality in Public Health, 2020)
Hospitals are required to always improve the quality of service provided to patients. These challenges have forced the hospital to develop its ability to manifest in various aspects of health care quality responsible. One of them by applying the assessment and early detection in patients kegawatan as well as the critical state of activation becomes very important. Quick and proper response to a nurse against the worsening conditions of patients giving a great impact to the quality of the quality of service provided. The purpose of this research is to analyze the implementation of Early Warning systems (EWSS) Score against AvLOS and trust patients in Inpatient installation at Jombang General Hospitals. The research design was analytic observational with a quantitative approach. Research variables i.e. implementation of EWSS as independent variables. AvLos and trust patients as the dependent variable. The population of this entire research nurses in Inpatient installation at Jombang General Hospitals as much as 135 nurses, patients and families of patients who are being treated in Inpatient installation at Jombang General Hospitals Jombang. Samples taken with the cluster random sampling technique as much as 101 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with logistics regression test. Logistic regression results indicate that partially and simultaneously show that the value of p values < 0.05 so that there were the implementation of Early Warning systems (EWSS) Score against AvLOS and trust of the patient, and the simultaneous influence of 83.2%. The existence of implementation of EWSS in patients with good then early detection and response officers can be done in a proper and effective against the condition and the healing of patients and can shorten the day care patients, so that it can affect the confidence and trust family and patient in receiving health services in the hospital